Challenges in safe environmental applications of biochar: identifying risks and unintended consequence - Mingying Dong; Mengyuan Jiang; Lizhi He; Zirun Zhang; Williamson Gustave; Meththika Vithanage; Nabeel Khan Niazi; Bo Chen; Xiaokai Zhang; Hailong Wang; Feng He (Biochar)
Abstract Over the past 10–15 years, biochar has garnered significant global attention in agriculture and environmental science. While most research has focused on the benefits of biochar application in soil enhancement, water quality improvement, and climate change mitigation, the potential risks associated with its use have often been overlooked. This oversight is critical, as the environmental fate of biochar is contingent upon understanding these risks. Once released into the environment, biochar can interact with environmental media, potentially releasing associated pollutants and threatening ecosystems. Therefore, it is essential to evaluate the unintended environmental and health risks associated with biochar during its production and application to select appropriate types for sustainable development. This review was conducted by systematically analyzing and synthesizing relevant studies from Web of Science, focusing on recent advancements and key debates in the field. It categorizes biochar risks into endogenous and exogenous risks based on the source of pollutants carried by biochar. The review analyzes in detail the impacts of raw materials, preparation processes, and application scenarios on the unintended environmental risks of biochar. Furthermore, it provides a thorough overview of the adverse effects on animals, plants, microorganisms, and human health, elucidating the mechanisms of pollutant release, aging, and nano-effects from environmental geochemical processes involving biochar. Additionally, this review summarizes the environmental risk assessment methods of biochar, providing a reference for its safe application and the sustainable development of biochar-related research. Graphical Abstract